Oligoethylene Glycol Side Chains Increase Charge Generation in Organic Semiconductor Nanoparticles for Enhanced Photocatalytic Hydrogen Evolution. Issue 22 (26th November 2021) - Kosco, Jan; Gonzalez‐Carrero, Soranyel; Howells, Calvyn T.; Zhang, Weimin; Moser, Maximilian; Sheelamanthula, Rajendar; Zhao, Lingyun; Willner, Benjamin; Hidalgo, Tania C.; Faber, Hendrik; Purushothaman, Balaji; Sachs, Michael; et al.
Abstract: Organic semiconductor nanoparticles (NPs) composed of an electron donor/acceptor (D/A) semiconductor blend have recently emerged as an efficient class of hydrogen‐evolution photocatalysts. It is demonstrated that using conjugated polymers functionalized with (oligo)ethylene glycol side chains in NP photocatalysts can greatly enhance their H2 ‐evolution efficiency compared to their nonglycolated analogues. The strategy is broadly applicable to a range of structurally diverse conjugated polymers. Transient spectroscopic studies show that glycolation facilitates charge generation even in the absence of a D/A heterojunction, and further suppresses both geminate and nongeminate charge recombination in D/A NPs. This results in a high yield of photogenerated charges with lifetimes long enough to efficiently drive ascorbic acid oxidation, which is correlated with greatly enhanced H2 ‐evolution rates in the glycolated NPs. Glycolation increases the relative permittivity of the semiconductors and facilitates water uptake. Together, these effects may increase the high‐frequency relative permittivity inside the NPs sufficiently, to cause the observed suppression of exciton and charge recombination responsible for the high photocatalytic activities of the glycolated NPs. Abstract : Employing conjugated polymers functionalized with (oligo)ethylene glycol side chains in nanoparticle photocatalysts can greatly enhance their H2 ‐evolution efficiency. Glycolation facilitates charge generation and suppresses both geminate and nongeminate charge recombination in donor/acceptor nanoparticles. This results in a high yield of photogenerated charges with lifetimes long enough to efficiently drive ascorbic acid oxidation and H2 evolution.